2016
DOI: 10.2147/ndt.s99577
|View full text |Cite
|
Sign up to set email alerts
|

Neuroleptic-induced deficit syndrome in bipolar disorder with psychosis

Abstract: Neuroleptics can induce not only physical adverse effects but also mental effects that produce deficit status in thought, affect, cognition, and behavior. This condition is known as neuroleptic-induced deficit syndrome (NIDS), which includes apathy, lack of initiative, anhedonia, indifference, blunted affect, and reduced insight into disease. Although this old concept now appears almost forgotten, neuroleptics, whether typical or atypical, can make depression or bipolar disorder resemble other more refractory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
(11 reference statements)
0
7
0
Order By: Relevance
“…The search strategy resulted in a total of 9 articles that met the inclusion criteria and were thus included in this review, informing data from a total of 1282 BD subjects. Four reports included only BD subjects (6,46,49,50), three explored compliance (6,33,49) and only three had a prospective design (6,29,49). Given the nature of the found data, it was not possible to perform a quantitative analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The search strategy resulted in a total of 9 articles that met the inclusion criteria and were thus included in this review, informing data from a total of 1282 BD subjects. Four reports included only BD subjects (6,46,49,50), three explored compliance (6,33,49) and only three had a prospective design (6,29,49). Given the nature of the found data, it was not possible to perform a quantitative analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Ueda et al [50] reported a series of three clinical vignettes on which neuroleptic deficit syndrome (NIDS) was superimposed with a depressive episode in BD patients treated with second-generation AP. In these cases, the NIDS included apathy, lack of initiative, emotional blunting, indifference and, more interestingly, poor insight into disease with a reduced desire to improve.…”
Section: Resultsmentioning
confidence: 99%
“…Australian & New Zealand Journal of Psychiatry,56(5) indifference, apathy, amotivation anhedonia and blunted affect (Ueda et al, 2016). NIDS may be considered associated with, or analogous to, what others have termed 'tardive dysmentia' -a state of affective blunting, reduced activation and diminished interpersonal activity (Wilson et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…In the nigrostriatal pathway, we may see TD – that is, persistent, repetitive, abnormal involuntary movements, often of the lips and tongue (Teo et al, 2012). In the mesocortical pathway we may see ‘neuroleptic-induced deficit syndrome’ (NIDS) – a state of emotional indifference, apathy, amotivation anhedonia and blunted affect (Ueda et al, 2016). NIDS may be considered associated with, or analogous to, what others have termed ‘tardive dysmentia’ – a state of affective blunting, reduced activation and diminished interpersonal activity (Wilson et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Although antipsychotics are usually first choice among drugs in psychosis, they are often insufficient [72]. Moreover, they may induce an “anti-joy-of-life” effect [73] or deficit syndrome resembling negative symptoms [74], and in the long run carry the risks of tardive psychosis [22, 75] and lower functional remission rate [76, 77]. Antidepressants may reduce negative symptoms [78] and suicide in schizophrenia [79, 80], and in one study reduced transition to psychosis in high-risk subjects more than antipsychotics [81], consistent with psychotic experiences being a marker foremost of affective dysregulation [82].…”
Section: Introductionmentioning
confidence: 99%